1984
DOI: 10.1172/jci111440
|View full text |Cite
|
Sign up to set email alerts
|

Role of hydrogen peroxide in the neutrophil-mediated release of prostacyclin from cultured endothelial cells.

Abstract: Abstract. We have examined the effect of activated neutrophils on the release of prostacyclin (PGI2) from cultured endothelial cells by radioimmunoassay and thin layer chromatography of its stable metabolite, 6-keto-prostaglandin Fla (6-keto-PGFI,a). Phorbol myristate acetate-activated neutrophils induced a time-and dose-dependent release of 6-keto-PGFIa from human and bovine endothelial cell monolayers, whereas phorbol myristate acetate alone and neutrophils alone did not. Pretreatment of the endothelial cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
2

Year Published

1985
1985
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(49 citation statements)
references
References 38 publications
3
44
0
2
Order By: Relevance
“…3) (66). Consistent with this, we found that H202 induced the coordinate accumulation of PAF and 6-keto-PGF,a (see Results) confirming earlier observations that H202 can stimulate PGI2 synthesis by EC (7,43) as well as our previous finding that PAF and PGI2 synthesis are initiated in concert in activated endothelium (22,23,33). These findings suggest that H202 induces Ca2+ flux, activation of phospholipase A2 (thought to be a Ca2+-dependent enzyme), and the hydrolysis of one or more membrane phospholipid precursors in endothelium, yielding free arachidonate and lyso-PAF for subsequent conversion to PGI2 and PAF, respectively (Whatley et al., manuscript submitted for publication).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…3) (66). Consistent with this, we found that H202 induced the coordinate accumulation of PAF and 6-keto-PGF,a (see Results) confirming earlier observations that H202 can stimulate PGI2 synthesis by EC (7,43) as well as our previous finding that PAF and PGI2 synthesis are initiated in concert in activated endothelium (22,23,33). These findings suggest that H202 induces Ca2+ flux, activation of phospholipase A2 (thought to be a Ca2+-dependent enzyme), and the hydrolysis of one or more membrane phospholipid precursors in endothelium, yielding free arachidonate and lyso-PAF for subsequent conversion to PGI2 and PAF, respectively (Whatley et al., manuscript submitted for publication).…”
Section: Discussionsupporting
confidence: 91%
“…), we considered the possibility that the activity was H202. H202 is generated by neutrophils activated by IoA or PMA, and can alter membrane phospholipids in EC (7,43 Table I). Inactivation of catalase by boiling prevented the inhibition (Table I).…”
Section: Measurements Ofec Injury and Cytotoxicitymentioning
confidence: 99%
“…6 would appear to be due to the progressively increasing levels of H202. (31,32,35) or in inhibition of this enzyme as our present data indicate. The ambient peroxide level in a cell is determined by a number of factors including the glutathione redox cycle (3, 30).…”
Section: Resultssupporting
confidence: 83%
“…These experiments suggest a second possible mechanism for peroxide stimulation of prostaglandin production: the activation of inflammatory or mesenchymal cells. H202, myeloperoxidase, and eosinophilic peroxidase will stimulate PGE2 and/ or PGO2 production in mast cells (30-33), fibroblasts (34,35), renal gomerular mesangial cells (36), and cultured endothelial cells (37,38). The mechanism of this stimulation is unclear, but in the endothelial cells it seems to involve gating of Ca2+ across the cell membrane either as the result of a receptor-mediated event or secondary to lipid peroxidation of the cell membrane, making it more permeable to Ca2+ with subsequent liberation of AA from membrane stores (38 (4,39).…”
Section: Discussionmentioning
confidence: 99%